Poincare-Lie algebra and noncommutative differential calculus - Güven, Z; Can, Z; Mir-Kasimov, R; Oguz, O (MAIK NAUKA/INTERPERIODICA PUBL, 2001)
A realization of Poincare-Lie algebra in terms of noncommutative differential calculus was constructed. Corresponding relativistic quantum mechanics was considered. (C) 2001 MAIK Nauka/Interperiodica.
Keywords: GEOMETRY; SPACE; QUANTIZATION; Physics